Electric dipole moment of the tau lepton revisited - Bernreuther, Werner; Chen, Long; Nachtmann, Otto (Physical review, 2021)
We reconsider the issue of the search for a nonzero electric dipole form factor (EDM) dτ(s) using optimal observables in τ+τ− production by e+e− collisions in the center-of-mass energy range from the τ-pair threshold to about √s∼15 GeV. We discuss the general formalism of optimal observables and apply it to two CP-odd observables that are sensitive to the real and imaginary part of dτ(s), respectively. We compute the expectation values and covariances of these optimal CP observables for τ-pair production at √s=10.58 GeV with subsequent decays of τ± into major leptonic or semihadronic modes. For the τ decays to two pions and three charged pions we take the full kinematic information of the hadronic system into account. Assuming that the Belle II experiment at the KEKB accelerator will eventually analyze data corresponding to an integrated luminosity of 50 ab−1 and applying acceptance cuts on the final-state pions, we find that 1 s.d. sensitivities δRedτ=6.8×10−20 e cm and δImdτ=4.0×10−20 e cm can be obtained with events where both τ’s decay semihadronically. We consider also the ideal case that no cuts on the final-state particles are applied. With 50 ab−1 at √s=10.58 GeV corresponding to 4.5×1010 τ+τ− events we find the 1 s.d. sensitivities δRedτ=5.8×10−20 e cm and δImdτ=3.2×10−20 e cm, again for events where both τ leptons decay semihadronically. Furthermore, we analyze the potential magnitude of the τ EDM form factor in the type-II two-Higgs doublet extension and in two scalar leptoquark extensions of the Standard Model, taking into account phenomenological constraints.
Gesehen am 28.07.2021